Rice cultivation changes and its relationships with geographical factors in Heilongjiang Province, China - Zhong-jun LU; Qian SONG; Ke-bao LIU; Wen-bin WU; Yan-xia LIU; Rui XIN; Dong-mei ZHANG (Journal of Integrative Agriculture, 2017)
Abstract: Rice planting patterns have changed dramatically over the past several decades in northeast China (NEC) due to the combined influence of global change and agricultural policy. Except for its great implications for environmental protection and climate change adaption, the spatio-temporal changes of rice cultivation in NEC are not clear. In this study, we conducted spatio-temporal analyses of NEC's major rice production region, Heilongjiang Province, by using satellite-derived rice cultivation maps. We found that the total cultivated area of rice in Heilongjiang Province increased largely from 1993 to 2011 and it expanded spatially to the northern and eastern part of the Sanjiang Plain. The results also showed that rice cultivation areas experienced a larger increase in the region managed by the Reclamation Management Bureau (RMB) than that managed by the local provincial government. Rice cultivation changes were closely related with those geographic factors over the investigated periods, represented by the geomorphic (slope), climatic (accumulated temperature), and hydrological (watershed) variables. These findings provide clear evidence that crop cultivation in NEC has been modified to better cope with the global change.